2019
DOI: 10.1016/j.worlddev.2018.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Structural reforms and firms’ productivity: Evidence from developing countries

Abstract: This paper assesses the effects of structural reforms on firm-level productivity for 37 developing countries from 2006 to 2014 period. It takes advantage of the IMF Monitoring of Fund Arrangements dataset for reform indexes and the World Bank Enterprise Surveys for firm-level productivity. The paper highlights the following results. Structural reforms such as financial, fiscal, real sector, and trade reforms, significantly improve firm-level productivity. Interestingly, real sector reforms have the most sizeab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 46 publications
1
12
0
1
Order By: Relevance
“…Overall, the findings in Table 3 highlight that in general financial sector, product markets, and trade reforms have increased the growth rate of labor productivity in developing countries. This result is in line with previous research that showed a positive relationship between structural reforms and economic growth (Prati et al, 2013), labor productivity growth (Dabla-Norris et al, 2016), and firm productivity growth (Kouamé & Tapsoba, 2019). The estimated coefficient on the logarithm of the initial level of productivity (LnProd(t-1)) is negative and statistically significant across the columns, indicating a convergence process in our data where countries with a lower level of labor productivity growth tend to grow faster and therefore are likely to catch up to countries with a higher level of productivity.…”
Section: Reforms and Aggregate Labor Productivity Growthsupporting
confidence: 93%
See 1 more Smart Citation
“…Overall, the findings in Table 3 highlight that in general financial sector, product markets, and trade reforms have increased the growth rate of labor productivity in developing countries. This result is in line with previous research that showed a positive relationship between structural reforms and economic growth (Prati et al, 2013), labor productivity growth (Dabla-Norris et al, 2016), and firm productivity growth (Kouamé & Tapsoba, 2019). The estimated coefficient on the logarithm of the initial level of productivity (LnProd(t-1)) is negative and statistically significant across the columns, indicating a convergence process in our data where countries with a lower level of labor productivity growth tend to grow faster and therefore are likely to catch up to countries with a higher level of productivity.…”
Section: Reforms and Aggregate Labor Productivity Growthsupporting
confidence: 93%
“…ElFayoumi et al ( 2018) focus on structural reforms and sectoral labor reallocation, neglecting the impact of reforms on intra-sectoral allocative efficiency. There are also existing studies at the firm-level that assess the impact of structural reforms on productivity growth in developing countries (Kouamé & Tapsoba, 2019;Amiti & Konings, 2007;Arnold et al,2016;Eslava et al, 2004;and Topalova & Khandelwal, 2011). Our paper differs from those papers mentioned above by focusing on the impact of reforms on productivity growth in developing countries at the macroeconomic level, where existing evidence is needed, but limited.…”
Section: Introductionmentioning
confidence: 98%
“…Successful industrialization in developing countries is due not only to the presence of institutions, but also to their ability to combine the initial economic conditions of the country to promote macroeconomic and institutional stability [4]. This ability is realized through financial, fiscal, sector and trade reforms, which complement each other to increase the productivity of firms [5] and reduce wage inequality in the framework of the General equilibrium approach [6], when the utility functions for the period are either additive or satisfy the replacement condition.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We focus on structural benchmarks recorded in the MONA database, which are non-quantifiable reform measures that are critical to achieving program goals, assuming that they represent major structural reform episodes. We organize the structural benchmarks obtained from the MONA database into three categories according to their impact on the fiscal, financial, and real sectors as shown in Table 2 (see also Kouamé and Tapsoba, 2018). To construct the indicators of structural reforms that will be used together with the indicator of trade liberalization, we apply the centered-reduced normalization method as in OECD (2008).…”
Section: Trade Liberalization Indicatorsmentioning
confidence: 99%
“…The macroeconomic environments in economies undertaking trade reforms could vary significantly and affect market power in a way that trade liberalization indicators alone cannot capture. We account for this by controlling for non-tariff trade barriers, an array of macro-level factors including for instance the income level, output growth, institutional quality and economic uncertainty, and also other structural reforms that may enhance or limit the relationship of international trade with domestic competition (Christiansen et al, 2009;Spilimbergo et al, 2009;Bordon et al, 2016;Dabla-Norris et al, 2016;ElFayoumi et al, 2018;Kouamé and Tapsoba, 2018). We find that institutional characteristics and concurrent reforms do have an effect on domestic market power, represented by firm level markups, but trade reform remains a salient factor to shape the market power of firms.…”
Section: Introductionmentioning
confidence: 99%